2009
DOI: 10.1021/jp9010263
|View full text |Cite
|
Sign up to set email alerts
|

Proton Dynamics in Layered Double Hydroxides: A 1H T1 Relaxation and Line Width Investigation

Abstract: The investigation of the dynamics of water and organic species confined in minerals or adsorbed at their surface is of significant geochemical, environmental, catalytic, biomedicine, and life's growth interests but is poorly understood on the molecular scale. This work explores the behavior of water molecules and glutamate species adsorbed on and between the double hydroxide layers of hydrotalcite [HT; (Mg 2 Al)(OH) 6 A -· nH 2 O, where A -is a counteranion which may bear different charges] and compares the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The overall solvation, and consequently the redox potential, seem to have a maximum value for mono-hydrated ions. A similar effect, in which the different stabilization of mono-and divalent anions intercalated in HT was compensated by other solvating agents was observed also for glutamate anions [46,47]. The changes of DE reported in Table 2 column 3 are quite pronounced, reflecting the different solvation of the two anions: when the interlayer distance grows, iodide solvation is affected much more than triiodide, and the reaction is markedly shifted to the right.…”
Section: Resultssupporting
confidence: 58%
“…The overall solvation, and consequently the redox potential, seem to have a maximum value for mono-hydrated ions. A similar effect, in which the different stabilization of mono-and divalent anions intercalated in HT was compensated by other solvating agents was observed also for glutamate anions [46,47]. The changes of DE reported in Table 2 column 3 are quite pronounced, reflecting the different solvation of the two anions: when the interlayer distance grows, iodide solvation is affected much more than triiodide, and the reaction is markedly shifted to the right.…”
Section: Resultssupporting
confidence: 58%
“…Likewise, many recent solid-state NMR studies have presented various results on structural and dynamical aspects in the chemistry of LDHs. Some of the most recent investigations based on modern innovations revealed deep insights into the structure of the cationic sheets of Mg II /Al III -, Zn II /Al III -, and Mg II /Ga III -based LDH materials including cationic order and layer/interlayer interface. Moreover, structure and dynamics of adsorbed and intercalated anions as well as water molecules were widely studied by solid-state 1 H, 13 C, 15 N, and 35 Cl NMR spectroscopy. …”
Section: Introductionmentioning
confidence: 99%
“…In several papers, Kirkpatrick et al have investigated the anions in LDHs, especially focused on dynamics by solid-state NMR. Studies include nitrate, chloride and carbonate ions in related Li 2 Al and Mg 3 Al-LDH. The presence of 27 Al nuclei in LDH materials makes them an easy target for NMR studies thanks to 27 Al’s high sensitivity in NMR. The NMR of quadrupolar nuclei has many features that make it suitable for dynamical and structural studies. For instance, measuring first- or second-order quadrupolar interactions can give crucial information on the nuclei’s chemical environment and dynamical behavior. NMR studies on LDHs have shown that as the electric charge density of the mineral layer decreases, there is a broader distribution of 27 Al environment ,, and that this distribution also has an effect on the inhomogeneous line width of the 27 Al solid-state NMR resonances, but so far, nothing has been investigated on the effects of dynamics on 27 Al spectra.…”
Section: Introductionmentioning
confidence: 99%